Structures, Energies, and Bonding Analysis of Monoaurated Complexes with N-Heterocyclic Carbene and Analogues - T.A.N. NGUYEN; T.P.L. HUYNH; T.X.P. VO; T.H. TRAN; D.S. TRAN; T.H. DANG; T.Q. DUONG (Universitas Gadjah Mada, 2015)
In this work, we computationally investigated from quantum chemical calculations (DFT) at the BP86 level with the various basis sets def2-SVP, def2-TZVPP, and TZ2P+, chemical bonding issues of the recently described carbene-analogues gold(I) complexes AuCl-NHEMe (Au1-NHE) with E = C – Pb. The optimized structures and the metal-ligand bond dissociation energy (BDE) were calculated, and the nature of the E?Au bond was studied with charge and energy decomposition methods. The equilibrium structures of the system showed that there were major differences in the bonded orientation from the ligands NHC-NHPb to gold(I) complex between the lighter and the heavier homologues. The BDEs results showed that the metal-carbene analogues bonds were very strong bonds and the strongest bond was calculated for Au1-NHC which had the bond strength De = 79.2 kcal/mol. Bonding analysis of Au1-NHE showed that NHE ligands exhibited donor-acceptor bonds with the ? lone pair electrons of NHE donated into the vacant orbital of the acceptor fragment (AuCl). The EDA-NOCV results indicated that the ligand NHE in Au1-NHE complexes were strong ?-donors and very weak ? donor and the bond order in complexes was Au1-NHC > Au1-NHSi > Au1-NHGe > Au1-NHSn > Au1-NHPb. We also realised that the gold-ligand bond was characterized by a ? back-donation component from the Au to the ligand. All investigated complexes in this study were suitable targets for synthesis and gave a challenge in designing Au nano-crystals of narrow size distribution from gold(I) complexes that carried versatile N-heterocyclic carbene-analogues NHE.